Diabetic macular edema - Cunha-Vaz, JG (2010)
Retinal edema is defined as any increase of water in retinal tissue resulting in an increase in its volume. This increase may be initially intracellular or extracellular. In the first case, there is cytotoxic edema. In the second, vasogenic edema, directly associated with an alteration of the blood-retinal barrier (BRB). Retinal thickness can now be measured, using the retinal thickness analyser (RTA). Similarly, local breakdown of the BRB can now be mapped using the retinal leakage analyser (RLA). The application of these methods to diabetic macular edema has shown that both types of retinal retinopathy edema occur in the initial stages of diabetic retinal disease. These observations suggest a role for neuroprotective and vasoprotective agents in the management of diabetic retinal disease.